2019
DOI: 10.1002/hed.25813
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of combined surgery and 125I seed brachytherapy for treatment of primary mucoepidermoid carcinoma of the parotid gland

Abstract: Background This study aimed to determine the effectiveness and safety of surgery combined with postoperative 125I seed brachytherapy for treatment of primary mucoepidermoid carcinoma (MEC) of the parotid gland. Methods Retrospective analysis of data of patients with MEC (n = 108) treated with surgery plus postoperative 125I seed brachytherapy between 2004 and 2016. Overall survival (OS), disease‐free survival (DFS), local control rate (LCR), distant metastasis, and radiation‐associated toxicities were analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…High-grade tumors are generally treated with surgical excision with wide margins or neck dissection followed by postoperative radiotherapy[ 13 ]. Furthermore, Wu et al[ 20 ] reported that postoperative adjuvant 125 I seed brachytherapy appears to be an effective and safe treatment option for MEC of the parotid gland with a clinically node-negative neck, especially when the tumor is of low or intermediate grade.…”
Section: Discussionmentioning
confidence: 99%
“…High-grade tumors are generally treated with surgical excision with wide margins or neck dissection followed by postoperative radiotherapy[ 13 ]. Furthermore, Wu et al[ 20 ] reported that postoperative adjuvant 125 I seed brachytherapy appears to be an effective and safe treatment option for MEC of the parotid gland with a clinically node-negative neck, especially when the tumor is of low or intermediate grade.…”
Section: Discussionmentioning
confidence: 99%
“…Another study reported that the median LTPFS time (14 vs. 9 months, p < 0.001) of I-125 BT in treating distant metastases in the oral and maxillofacial region compared to EBRT was also higher ( 86 ). Moreover, several single-arm clinical studies suggested that I-125 BT performed exceptionally well in various head and neck cancers, including primary mucoepidermoid carcinoma of the parotid gland (10-year OS rate of 95.8%), adenoid cystic carcinoma (ACC) involving the skull base (3-year OS rate of 62.6% and 3-year PFS rates of 46.4%), and salivary gland carcinomas of the lip and buccal mucosa (10-year LC rate of 82.9% and 10-year OS rate of 77.8%) ( 111 113 ). One study reported that the use of I-125 BT in non-squamous carcinoma results in a better outcome compared to squamous cell carcinoma ( 2 ).…”
Section: I-125 Brachytherapy In Solid Tumorsmentioning
confidence: 99%
“…TACE Median OS time: 11 vs. 9 months, P=0.022. Median biliary patency time: 6 vs. 4 months, P=0.Mean PFS time: 7.1 vs. 3.6 months; P<0.001; Mean OS time: 16.9 VS. 12.PFS time: 8 vs. 5.5 months; P < 0.05; LCR time: 10 vs. 6.2 months; P< 0.parotid gland (10-year OS rate of 95.8%), adenoid cystic carcinoma (ACC) involving the skull base (3-year OS rate of 62.6% and 3-year PFS rates of 46.4%), and salivary gland carcinomas of the lip and buccal mucosa (10-year LC rate of 82.9% and 10-year OS rate of 77.8%)(111)(112)(113).…”
mentioning
confidence: 99%
“…Despite the survival benefits of RT suggested in previous reports, this therapeutic approach is often limited by concerns about long‐term toxicity in children, such as xerostomia, trismus, development of secondary cancers, and craniofacial growth abnormalities 20,21 . 125 I interstitial brachytherapy (IBT) is an RT modality, where postoperative 125 I IBT delivers a high dose of radiation directly to target areas, minimizing nontarget dose dispersal to adjacent normal structures, and is increasingly reported as effective and safe for treating children with malignant PG tumors 22‐24 …”
Section: Introductionmentioning
confidence: 99%
“…20,21 125 I interstitial brachytherapy (IBT) is an RT modality, where postoperative 125 I IBT delivers a high dose of radiation directly to target areas, minimizing nontarget dose dispersal to adjacent normal structures, and is increasingly reported as effective and safe for treating children with malignant PG tumors. [22][23][24] The aim of this retrospective study was to analyze the effectiveness and safety of surgery combined with postoperative 125 I IBT among children and adolescents with AciCC of the PG with high-risk features.…”
mentioning
confidence: 99%